2016
DOI: 10.1371/journal.pone.0154732
|View full text |Cite|
|
Sign up to set email alerts
|

Taking Perspective: Personal Pronouns Affect Experiential Aspects of Literary Reading

Abstract: Personal pronouns have been shown to influence cognitive perspective taking during comprehension. Studies using single sentences found that 3rd person pronouns facilitate the construction of a mental model from an observer’s perspective, whereas 2nd person pronouns support an actor’s perspective. The direction of the effect for 1st person pronouns seems to depend on the situational context. In the present study, we investigated how personal pronouns influence discourse comprehension when people read fiction st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 45 publications
7
59
2
2
Order By: Relevance
“…In line with the previous literature (Hartung et al, 2016), we predicted that participants would display more narrative engagement for stories that were written in a first-person perspective than for stories that were written in a third-person perspective. Furthermore, we predicted that participants with higher levels of alexithymia would display less narrative engagement than participants with lower levels of alexithymia.…”
Section: The Present Research and Hypothesessupporting
confidence: 75%
See 1 more Smart Citation
“…In line with the previous literature (Hartung et al, 2016), we predicted that participants would display more narrative engagement for stories that were written in a first-person perspective than for stories that were written in a third-person perspective. Furthermore, we predicted that participants with higher levels of alexithymia would display less narrative engagement than participants with lower levels of alexithymia.…”
Section: The Present Research and Hypothesessupporting
confidence: 75%
“…As far as we know, this notion has been empirically tested in only one study to date. In this study, participants were asked to read literary stories that were written from either a first or a third person perspective (Hartung, Burke, Hagoort, & Willems, 2016). The findings showed that participants reported higher narrative engagement during stories that were written in a first-person perspective than for stories written in a third-person perspective.…”
Section: Narrative Engagement and Perspective Takingmentioning
confidence: 87%
“…The scores correlated r = .26 with empathy for depression (N = 210 students) and r = .11 with empathy for grief. Koopman's (2015) test was also used by Hartung, Burke, Hagoort, and Willems (2016), but seems to have been involved in one significant correlation only, namely the appreciation of the stories read (p < .05). Unfortunately, in neither article was information given about the reliability of the ART scores, so that it is difficult to evaluate the quality of the test.…”
Section: Non-english Author Recognition Testsmentioning
confidence: 99%
“…It is still unclear what the nature of the images evoked during literary reading is, how exactly they influence our reading experience, and how they impact appreciation and memory for narratives (but see Hartung et al, 2016). An important avenue for future research is to add to our understanding of the impact of our propensity for simulation on our fiction experience, for example, the dependence of LRI simulation on personal experiences (e.g., Burke, 2011).…”
Section: Mental Simulation and Imagerymentioning
confidence: 99%